"Bad Neighborhood" and Internet Adoption in Poor Countries: What is behind the Persistent Digital Gap?. (23rd August 2017) - Dohse, Dirk; Lim, Cheng Yee
Abstract: The paper investigates the determinants of Internet adoption in poor countries, focusing on the role of macro‐geographic location (neighborhood). It is argued that neighboring countries are interconnected by various kinds of spillovers, including knowledge spillovers as well as spillovers of norms and attitudes that affect individual adoption behavior. The empirical findings support the view that Internet adoption is affected by adoption rates in neighboring countries, even when controlling for a wide range of covariates. Addressing potential endogeneity concerns using an instrumental variable approach moreover suggests these relationships to be causal. The findings imply that international policies to support Internet adoption in poor countries might be more effective if they target groups of neighboring countries rather than single countries in order to better exploit spillovers between neighboring countries.